DANGEROUS EFFECTS OF TOXIC SUBSTANCES - M.Daliyev (Journal of new century innovations, 2024)
Abstract: Toxic substances are easily absorbed into all organs, including the brain, and can cause acute and chronic poisoning. Organic mercury compounds damage capillaries, causing dilation of blood vessels, increased permeability, and fluid transfer from blood to tissues, a process that exacerbates damage to the central nervous system. Compounds have a toxic effect on the heart, disrupt the regulation of heart activity.